Democracy – Community – Social justice: The Theory and Practice of the Polish Cooperative Movement Between the two World Wars - Piskała, Kamil (Praktyka Teoretyczna, 2018)
This article discusses the most recent publishing projects devoted to the history and intellectual accomplishments of the Polish cooperative movement before 1939. It illustrates the political dimension of the concept of cooperation, the need to deepen the research on the symbolic universe of the movement and the effect which defining the peripheral status of the Polish economy had on the development of the economic analyses of the Polish cooperators. The political philosophy of Polish cooperativism, created primarily by Edward Abramowski, in many respects exceeds the limitations characteristic for the classical modern ideologies of the political left-wing, thanks to which it inscribes in the process of ―inventing tradition‖ by the modern emancipation movements in Poland.